Effect of Use of Aluminum Foil Blanket Against Increased Body Temperature in Patients Hypothermia after Spinal Anesthesia in the Operation Room of the Sele Be Solu Hospital, Sorong West Papua (Medico Legal Update, 2020)
Local, general, and regional anesthesia is complex actions or events that cannot be separated from electiveor emergency surgery. Anesthesia affects the three thermoregulatory elements consisting of afferent inputelements, signal regulation in the central region, and also the efferent response which can lead to hypothermia.This study aims to determine the effect of the use of aluminum foil blankets on increasing body temperaturein hypothermia patients after spinal anesthesia. This study uses a Pre-Experimental study design with a PrePost Test Only Design approach. Sampling in this study used a purposive sampling technique. 12 sampleswere given the intervention to use aluminum foil blankets. Analysis of data using the Shapiro-Wilk test,Homogeneity of Lavene Test, and Paired sample T-Test. The results of statistical tests using the PairedSample T-Test obtained a p-value of less than 0.05 (